Effect of Feeding Dried Apple Pomace on Ruminal Fermentation, Methane Emission, and Biohydrogenation of Unsaturated Fatty Acids in Dairy Cows - Khaled Gadulrab; Pola Sidoruk; Martyna Kozłowska; Małgorzata Szumacher-Strabel; Dorota Lechniak; Paweł Kołodziejski; Jarosław Pytlewski; Nina Strzałkowska; Jarosław Olav Horbańczuk; Artur Jóźwik; Yulianri Rizki Yanza; Agung Irawan; et al. (Agriculture, 2023)
Industrial fruit by-products are now being utilized as animal feeds for several reasons. They may substitute the conventional cereal feeds, and also offer economic and environmental benefits. One of the most important industrial fruit by-products is apple pomace, which can be used as a source of energy in the ration of ruminant species, including dairy cattle. The aim of the present study was to evaluate the effect of feeding dried apple pomace to dairy cattle on ruminal fermentation, fatty acid concentration, microbial populations, and methane production. The experiment lasted 64 days and was conducted with 4 cannulated commercial dairy cows. The control animals received a standard diet, while the experimental animals was fed a standard diet supplemented with 150 g/kg DM dried apple pomace. Ruminal fluid samples were collected at three different time intervals. The samples were obtained at 0-, 3-, and 6-h post-feeding. The ruminal fluid was used to assess the ammonia concentration, pH, volatile fatty acids (VFA), long-chain fatty acids (FA), microbial population. A number of ruminal fermentation variables changed as a result of the addition of dried apple pomace to the standard diet. Ruminal pH slightly increased (p < 0.01) while the ammonia concentration decreased (p < 0.01) by 46%. There was a significant decrease in total protozoa count (p < 0.01) and an increase (p < 0.01) in total volatile fatty acids. In addition, there was a decline in methane emission (p = 0.05) by 8% due to dried apple pomace feeding. To sum up, this study demonstrated a positive effect of 150 g/kg DM dietary dried apple pomace on ruminal metabolism including a decrease in ammonia concentration and methane emissions, alongside with an increase in total ruminal VFAs, higher nutrient digestibility, and milk production. Also, beneficial changes to the ruminal fatty acid profile resulting from reduced biohydrogenation were observed although a decreased content of the C18:2 cis 9 trans 11 isomer was also noticed. The dietary inclusion of DAP can serve as a valuable, sustainable, and environmentally friendly dietary component for dairy cows.